Growth inhibition of Salmonella by Leuconostoc species isolated from buffalo milk curd (Annals of Bangladesh Agriculture, 2024)
Traditional fermented products are considered to be a niche for microbial diversity. Probiotics offer a unique approach for addressing the threat of antibiotic resistance. Therefore, the aim of the present study was to isolate Leuconostoc spp. from Buffalo milk curd, an artisanal fermented dairy product in Bangladesh and assess their growth inhibition competence against Salmonella sp. A total of 50 isolates were isolated and purified from five freshly prepared buffalo milk curd samples using two different media, with glucose or sucrose as the carbon source. Among these pure isolates, 37 were identified as presumptive Leuconostoc spp. The biochemical identification using the VITEK 2 system confirmed that 59.5% of the isolates were Leuconostoc mesenteroides ssp. cremoris, while 40.5% were Leuconostoc pseudomesenteroides. Out of the identified isolates, twelve had a similarity of over 97%, and twenty-five had a similarity of less than 96%. Consequently, these twelve isolates were tested for their antimicrobial activity against Salmonella sp. using two in vitro methods, agar well diffusion and microbroth. The isolate M1L1 exhibited the highest inhibitory zone (15 mm) and showed 55.6% growth inhibition by the agar well diffusion and microbroth assay, respectively, suggesting a similar efficacy between the two methods. Notably, five other isolates also displayed inhibitory zones ranging from 13 to 15 mm and growth inhibition percentages of 37 to 52%. Overall, the isolated Leuconostoc spp. could be utilized as probiotics to combat pathogenic microorganisms.Ann. Bangladesh Agric. (2023) 27 (1): 93-104